A general health promotion approach to helping smokers with non-communicable diseases quit smoking: A pilot randomized controlled trial - Li, William Ho Cheung; Ho, Laurie Long Kwan; Cheung, Ankie Tan; Wong, Man Ping; Cheung, Derek Yee Tak; Xia, Wei; Lam, Tai Hing (Frontiers in Public Health, 2022)
Background: Despite evidence showing that continued smoking in patients with non-communicable diseases can reduce treatment efficacy and increase the risk of disease progression and multimorbidity, many smoker patients either have no intention to quit or have had failed attempts at quitting. Objective: To ascertain the feasibility of a general health promotion approach that uses instant messaging to deliver brief motivational interviewing to help smokers with non-communicable diseases quit smoking. Methods: In total, 60 participants who had medical follow-up in a special out-patient clinic were randomised into two groups, 30 in the intervention group received brief motivational interviewing to assist them with their chosen behavioural changes, and 30 in the control group received only a smoking cessation booklet. The outcome measures included self-reported 7-day point prevalence of smoking abstinence and any behavioural change reported by the participants at 6 and 12 months. Biochemical validation was performed for those who verbally reported a 7-day point prevalence of smoking abstinence at 12 months. Results: The majority (95%) of smokers who attended the out-patient clinic owned a smartphone. The response rate was 73.2%. Retention rates at 6-month and 12-month follow-up were 83.3% and 71.7%, respectively. The process evaluation indicated that participants were satisfied with the content of the brief MI messages and appreciated the use of instant messaging as a way to provide them with professional advice and support for managing their health-related lifestyles. The intervention group had a higher biochemically validated abstinence rate than the control group at 12 months (16.7% vs 6.7 P=.23) although the difference was not statistically significant (Adjusted odd ratio 2.4, 95% confidence interval, 0.43–13.75; P=.32.), In addition, the proportion of participants reporting a behavioural change was slightly higher in the intervention group at 6 months. Conclusion: This study demonstrated the potential efficacy and feasibility of a general health promotion approach that uses instant messaging to deliver brief motivational interviewing to help smokers with non-communicable diseases quit smoking. The findings can be used to create a new smoking cessation service model that implements a flexible, proactive and personalised approach to help smokers quit smoking.